Single-Center Experience of Pulmonary Endarterectomy for Chronic Thromboembolic Pulmonary Hypertension: The Results from the Tabriz University Medical Sciences (TUMS) CTEPH Program - Parvizi, Rezayat; Bilehjani, Eisa; Mahmoudian, Babak; Koohi, Ata; Shojaan, Hooriah; Ansarin, Khalil; Rashidi, Farid (The Thoracic and Cardiovascular Surgeon, 2023)
Introduction Pulmonary endarterectomy (PEA) remains the preferred and potentially curative option for patients with chronic thromboembolic pulmonary hypertension (CTEPH). This study aimed to report the results of PEA for CTEPH in a tertiary center in Tabriz, Iran.Methods We analyzed the results of 42 CTEPH patients undergoing PEA, who were enrolled in the Tabriz University of Medical Sciences (TUMS-CTEPH) from January 2016 to October 2020. The main outcome measures included the New York Heart Association (NYHA) functional classification, the 6-Minute Walk Distance, hemodynamic measures in right heart catheterization, morbidity, and mortality.Results There was a significant improvement in the NYHA function class (2.6 ± 0.5 vs 1.1 ± 0.34), mean pulmonary arterial pressure (47.1 ± 13 vs 27.9 ± 8 mm Hg), cardiac output (4.3 ± 1.06 vs 5.9 ± 1.2 L/min), and pulmonary vascular resistance (709.4 ± 297.5 vs 214 ± 77 dyn s/cm5). Fifteen patients (35%) developed complications. The most common complication (10 [23%]) was reperfusion injury. Also, postsurgical mortality was 4% during hospital admission and 1-year follow-up.Conclusion This is the first single-center report of PEA from Iran. Post-PEA and 1-year survival were acceptable as a referral center. PEA can be performed safe with low mortality. Greater awareness of PEA and patients' access to experienced CTEPH centers are important issues.
Keywords: pulmonary hypertension; thromboendarterectomy; chronic thromboembolism